Effects of dietary energy density and lysine:calorie ratio on the growth performance of growing pigs and subsequent finishing performance - J W Smith II; P R O'Quinn; Michael D Tokach; Robert D Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1997)
One hundred twenty crossbred gilts were used in a growth trial to evaluate the effects of increasing dietary energy density and lysine:calorie ratio on growing pig growth performance and subsequent finishing performance. Feeding 3% choice white grease and 3.45 g lysine:Mcal ME maximized growth performance of growing gilts. Choice white grease additions and increasing lysine:calorie ratio during growing (65 to 160 lb) did not affect carcass back fat or loin depth at 235 lb.; Swine Day, Manhattan, KS, November 20, 1997
Keywords: Swine day; 1997; Kansas Agricultural Experiment Station contribution; no. 98-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 795; Swine; Feed:gain ratio; Energy density; Lysine:calorie ratio; Growing-finishing pigs